Family science, land‐grant universities, and the daunting legacy of the land‐grab institution. - Ambo, Theresa J.; Gavazzi, Stephen M. (Journal of Family Theory & Review, 2025)
This paper wrestles with the nexus of settler colonialism, the expropriation of Indigenous lands to establish the United States land‐grant system, and the field of Family Science. Family Science programs are embedded within the power structures of the universities to which they belong; certain characteristics of these academic units—especially their emphasis on engagement and professional credentialing—theoretically could produce an idiosyncratic and nuanced context in which academy members operate. First, we grapple with the history of US settler colonialism and the land‐grab concept, focusing attention on the enormous transfer of Native American lands into universities through the Morrill Act. Second, we examine the convergence between the applied activities of family scientists and the tripartite land‐grant mission of teaching, research, and engagement. Consequently, our final aim is to investigate the impact of being a family scientist within a land‐grant university grappling with the historical injustices surrounding its foundation.